Parallelized Biomass Monitoring of two Distinct Kluyveromyces Marxianus Strains in Shake Flask Cultivation (London Journal of Medical and Health Research, 2023)
Kluyveromyces marxianus, a non-conventional yeast, carries traits deemed suitable for industrial applications, such as ethanol production, exhibiting advantages over Saccharomyces cerevisiae in terms of growth rate and thermotolerance. Non-invasive parallel monitoring of biomass in shake flask cultures allows for efficient microorganism characterization, providing much-needed and accurate data on these strains through continuous sampling. Therefore, this study aimed to assess the behavior of two K. marxianus strains during continuous shake flask cultivation. Strain IZ 1339 exhibited a constant, however, slower growth pattern when compared to strain FT 146L, which grew constantly up until the 12 h, after that the strain presented flocculation, affecting the quality of the readings. Strain IZ 1339 also had a higher ODmax value when compared to FT 146L, nevertheless, their growth rate was similar, showing that both strains had a satisfactory performance in both concentrations of molasses. Non-invasive monitoring makes it possible to accompany the growth pattern of the strains, indicating that both K. marxianus strains perform well when grown in a sugarcane molasses medium. This feature makes these K. marxianus strains an interesting non-conventional alternative to S. cerevisiae when it comes to industrial application.
Keywords: Fixed-dose; Quality by Design; Tablets; Design space; Critical quality attributes.